Ethics of resuscitation for extremely premature infants: a systematic review of argument-based literature - Cavolo, Alice (Journal of medical ethics, 2021)
Objective To present (1) the ethical concepts related to the debate on resuscitation of extremely premature infants (EPIs) as they are described in the ethical literature; and (2) the ethical arguments based on these concepts.Design We conducted a systematic review of the ethical literature. We selected articles based on the following predefined inclusion/exclusion criteria: (1) English language articles (2) presenting fully elaborated ethical arguments (3) on resuscitation (4) of EPIs, that is, infants born before 28 weeks of gestation.Analysis After repeated reading of articles, we developed individual summaries, conceptual schemes and an overall conceptual scheme. Ethical arguments and concepts were identified and analysed.Results Forty articles were included out of 4709 screened. Personhood, best interest, autonomy and justice were concepts grounding the various arguments. Regarding these concepts, included authors agreed that the best interest principle should guide resuscitation decisions, whereas justice seemed the least important concept. The arguments addressed two questions: Should we resuscitate EPIs? Who should decide? Included authors agreed that not all EPIs should be resuscitated but disagreed on what criteria should ground this decision. Overall, included authors agreed that both parents and physicians should contribute to the decision.Conclusions The included publications suggest that while the best interest is the main concept guiding resuscitation decisions, justice is the least important. The included authors also agree that both parents and physicians should be actively involved in resuscitation decisions for EPIs. However, our results suggest that parents’ decision should be over-ridden when in contrast with the EPI’s best interest.All data relevant to the study are included in the article or uploaded as supplementary information.